Mucin expression in pancreatic ductal adenocarcinoma cell lines in 2D and 3D cultures: A proteomic and immunocytochemical analysis - Yuuki Shichi; Hiroki Tsumoto; Masakazu Fujiwara; Keisuke Nonaka; Yasuko Hasegawa; Seiichi Shinji; Hirofumi Rokutan; Kimimasa Takahashi; Tomio Arai; Yuri Miura; Toshiyuki Ishiwata (PLoS ONE, 2026)
Pancreatic ductal adenocarcinoma (PDAC) exhibits diverse phenotypes, including epithelial and mesenchymal characteristics, yet these features have not been effectively translated into clinical applications. Mucins are implicated in tumor progression and therapeutic resistance and are considered potential diagnostic and therapeutic targets. In this study, five epithelial and three mesenchymal PDAC cell lines were cultured under two-dimensional (2D) and three-dimensional (3D) conditions to investigate mucin expression. Proteomic analysis identified five mucins (MUC1, MUC4, MUC5B, MUC19, and MUC20) in 2D culture and eight (including MUC2, MUC5AC, and MUC13) in 3D culture. Candidate mucins were further validated by immunocytochemistry with H-score assessment. MUC1 was consistently expressed in all PDAC cell lines and showed marked upregulation in several lines under 3D culture. In mesenchymal PDAC cell lines, mucin expression was largely restricted to MUC1, whereas epithelial lines displayed broad 3D-induced reorganization. Notably, MUC5AC was absent in 2D culture but robustly induced in all epithelial PDAC cell lines under 3D conditions. Other mucins, including MUC2, MUC4, MUC5B, MUC13, MUC19, and MUC20, were variably upregulated, with epithelial lines demonstrating higher diversity and intensity of expression. These findings demonstrate that 3D culture effectively reveals the plasticity and heterogeneity of mucin expression in PDAC, highlighting its potential as a platform for biomarker discovery and the development of therapeutic strategies.